Methodological Aspects of Assessing the Quality of Life of Re-gions’ Residents - Dmitrievich Burykin, Alexey; Vitalievna Zholudeva, Vera; Evgenievna Kuzmina, Evgenia; Fedorovna Melnichenko, Nadezhda; Anatolievich Lebede, Konstantin; ., . (International Journal of Engineering and Technology, 2018)
The paper is devoted to developing a set of techniques for assessing the quality of life in regions. The authorsâ€™ proposed system of indicators is not universal, but it does help to demonstrate the significance of social partnership at the regional level. The studyâ€™s findings help to come to the conclusion that a crucial objective is to cultivate in people the knowledge about human rights and decent work, their own rights and ways to protect them, social protection. The authors prove that assessments of quality of life depend on both a regionâ€™s economic characteristics and its residentsâ€™ overall satisfaction with life, work, healthcare, and environmental conditions. The authorsâ€™ study has revealed that in the climate of social and economic instability the process of improving peopleâ€™s quality of life requires substantial modernization, primarily in the area of determining specific directions and ways of diversifying the key sources of moral satisfaction and income of the population. Â Â